The Level of Knowledge of Decompression Sickness among Divers in Saudi Arabia – A Cross-sectional Study - Maan Jamjoom; Bsaim Altirkistani; Faisal Al-Jadani; Hashem Mirza; Majed Alhijjy; Reem Abdullah Alharthi; Ilana Hakeem; Anass Madani (Journal of Marine Medical Society, 2024)
Introduction: Decompression sickness (DCS) is a clinical syndrome, i.e. commonly seen in divers. The global prevalence of DCS among professional dive instructors is approximately 3.4%. This study aimed to assess the level of knowledge concerning DCS among divers in Saudi Arabia. Materials and Methods: This is a cross-sectional study conducted among divers in Saudi Arabia. The research team visited several diving resorts to distribute the questionnaires. Furthermore, diving instructors from different cities across the nation were requested to distribute the questionnaire to their colleagues and diving communities. Results: A total of 262 divers participated in the study, of which 252 (96.18%) had a scuba-certified license. The majority of divers (94.27%) reported that they were aware of DCS. Furthermore, 27.48% of the participants reported that they had experienced clinical symptoms of DCS. Only 14 (19.44%) received first aid care, and 17 (6.489%) needed a deco dive/decompression dive. Females demonstrated a higher risk of developing DCS-related symptoms than males (odds ratio = 2.57; 95% confidence interval = 5.44–1.21; P = 0.0135). Conclusion: Majority of the participants were familiar with the nature of the disease and were found to have practiced safe diving. Practically, one-quarter of the participants experienced DCS-related symptoms, and only very few of them received first aid and/or a deco dive. Despite the nature of the study and its small sample size, this study adds to the growing nature of published literature in giving a better understanding of the disease by divers.